The Role of the Public Works and Spatial Planning Department in the Spatial Plan Local Regulations of Asahan Regency - Nasution, Emmi Rahmiwita; Purnamawati, Evi; Situmorang, Robinson (West Science Law and Human Rights, 2024)
This study focuses on the Public Works and Spatial Planning Office's role in the existing Spatial Planning Regional Regulation in Asahan Regency, especially in its amendments. The changes are intended to harmonize, synchronize and harmonize the spatial planning regulations that the Regional Government of North Sumatra Province has issued. The research method used is the empirical method, considering the Settlement of the Formation of the Civil Code, and the empirically symptomatic law. These, namely various legal factors influence it, so the study will lead to the role of organizations and legal institutions when enforcing the law. The results show that changes to the Asahan District Civil Code have been implemented based on the proposals from the PUPR Service so that the role of the PPUPR Office has been achieved, namely planning, informative, and indicative. For implementation, there are also obstacles encountered, such as the limited budget ceiling, the issuance of changes to the Procedure for the Implementation of Strategic Environmental Studies (KLHS), the limited number of employees in the field of spatial planning who have spatial planning legal competence and the lack of financial support for education and training in the field of spatial planning by local governments.